How to Report Systematic Review Studies; A Critical Review of Some Methodological Issues and Recommendations to Consider When Conducting These Studies - Mehrdad Amir Behghadami; Ali Janati (Bulletin of Emergency and Trauma, 2019)
Dear editor, Recently a study titled, “A Productive Proposed Search Syntax for Health Disaster Preparedness Research”, was worked by Rastegarfar et al. in the Bulletin of Emergency And Trauma [1]. First of all, we would like to thank the editors that help to appear review study. In addition, we would like to extend our appreciation to the authors of this article. Review studies are considered as studies with the highest level of evidence that play an important role in evidence-based decision making [2]. The results of the mentioned study are an interesting; however, we believe that there are some questions regarding the study, which, we would like to present. These questions, if replied, will only apply to improve the quality of the current study and similar studies in the near future.